A Friction Stir Welding case study using Temperature Controlled Robotics with a HPDC Cylinder Block and dissimilar materials joining. (October 2019) - Silva-Magalhães, Ana; Cederqvist, Lars; De Backer, Jeroen; Håkansson, Emil; Ossiansson, Bruno; Bolmsjö, Gunnar
Highlights: Cast and wrought aluminium alloys were successfully joined by FSW to produce a cooling channel in a cylinder block. The joining of component with highly complex geometries was achieved by robotic FSW with process temperature control. An adquate weld procedure was achieved by using a reduced number of components, resulting in time and cost improvements. Abstract: The automotive industry is going through a radical transformation from combustion engines to fully electric propulsion, aiming at improving key performance indicators related to efficiency, environmental sustainability and economic competitiveness. In this transition period, it is important to continue the innovation of combustion engines for e.g. plug-in hybrid vehicles. This led Volvo Cars to pursue radically new manufacturing processes such as Friction Stir Welding (FSW). The work presented in this paper is a case study whereby feasibility of using FSW to join a reinforcement element into the aluminium casted Cylinder Block was studied. The complex geometry of the joint required a flexible five-axis manipulator, i.e. an industrial robot, as well as advanced process control, i.e. temperature feedback control, in order to maintain a consistent weld quality throughout the whole component. The process was successfully demonstrated in a lab environment and offers a cost-efficient solution while maintaining the durability and higher efficiency. The outcome of this study shows the great potential of implementing the FSW process in combination with High Pressure Die Casted components, such a Cylinder Block.